The Pluralism of Indonesian Criminal Law: Implications and Orientations in the Post-New Criminal Code - Heliany, Ina; Widowati, Widowati; Sihotang, Muhenri (SASI, 2023)
Introduction: The ratification of the New Criminal Code actually has an orientation towards strengthening legal pluralism in the field of criminal law. This is evidenced by the adoption of customary criminal law as a recognized law in addition to national criminal law.Purposes of the Research:  This study aims to analyze the implications of the formulation of Article 2 of the New Criminal Code concerning the practice of Indonesian criminal law pluralism and the future orientation of the formulation of Article 2 of the New Criminal Code to strengthen the pluralism of Indonesian criminal law.Methods of the Research: This research is a normative legal research that uses a concept and statutory approach.Results of the Research: The study results show that the legal implications of formulating guarantees for the enforceability of laws that live in society affirm the existence of customary criminal law as a living law in society, thereby affirming the essence of legal pluralism. The future orientation of Indonesian criminal law pluralism after the enactment of the New Criminal Code is to maintain harmonious relations between the national legal system and the customary law system and to conduct an inventory of existing customary criminal laws. Customary criminal law that still exists is then regulated specifically in regional regulations in each region so that judges can then use it as a reference in deciding a criminal case that has a legal essence that lives in society.